2021
DOI: 10.1097/md.0000000000026028
|View full text |Cite
|
Sign up to set email alerts
|

Occupational stress among Nigerian construction trade artisans in the building construction sector

Abstract: Background: Construction work can negatively affect artisans’ mental health in the form of stress. This research investigated the effect of cognitive behavioral intervention on occupational stress among Nigerian construction trade artisans in the building construction sector. Methods: In this randomized controlled study involving 3 waves of data collection, 140 construction trade artisans who presented with high occupational stress symptoms at the study onset were assig… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 24 publications
0
7
0
Order By: Relevance
“…RCT study involves the random assignment of participants to different treatment conditions (William, 2018). Similarly, Ogbuanya et al (2017a), (2017b), Nwokeoma et al (2019), Onyishi et al (2021), Ugwuanyi et al (2020a, 2020b, 2020c, 2020d), Ede et al (2020), Ogba et al (2020), Okide et al (2020), Umoke et al (2020), Agboeze et al (2020), Omeje et al (2021) have adopted the design in their recent studies.…”
Section: Methodsmentioning
confidence: 95%
“…RCT study involves the random assignment of participants to different treatment conditions (William, 2018). Similarly, Ogbuanya et al (2017a), (2017b), Nwokeoma et al (2019), Onyishi et al (2021), Ugwuanyi et al (2020a, 2020b, 2020c, 2020d), Ede et al (2020), Ogba et al (2020), Okide et al (2020), Umoke et al (2020), Agboeze et al (2020), Omeje et al (2021) have adopted the design in their recent studies.…”
Section: Methodsmentioning
confidence: 95%
“…For example, Campbell and Gunning (2020) identified a diverse list of strategies that employers could adopt to improve mental wellbeing that centre around the causes of poor mental health, for example, establishing manageable workloads to reduce job stress and ensure good work-life balance, maintaining a strong, supportive and inclusive culture that encourages positive professional relationships among all colleagues, zero tolerance for bullying and harassment. Omeje et al (2021) found that cognitive behavioural intervention effectively manages job stress in the construction industry. However, the longterm effectiveness of the intervention is inconclusive.…”
Section: Health Promotionmentioning
confidence: 99%
“…, 2017), workers in “blue-collar” jobs or occupations (Dong et al. , 2015), “operatives” (George and Loosemore, 2019) and “construction trade artisans” (Omeje et al. , 2021).…”
Section: Purpose and Scope Of Reviewmentioning
confidence: 99%
See 1 more Smart Citation
“…The construction industry in Nigeria is a signi cant employer of labour, engaging approximately 20% of the working population, with a majority of workers employed informally (NBS, 2018; Odediran & Babalola, 2013; Oni et al, 2022). Within this industry, formal workers, such as Engineers and Architects, primarily assume supervisory roles, while informal workers, commonly referred to as artisans, tradesmen, or labourers, carry out the labour-intensive tasks on construction sites (Omeje et al, 2021). Given the physical demands of construction work and the escalating youth unemployment rate in Nigeria, young people constitute a substantial portion of the workforce in this industry.…”
Section: Introductionmentioning
confidence: 99%